Role of Guanidine and Methylguanidine Hydrochloride on the Thermodynamic Stability and Internal Dynamics of Horse Ferrocytochrome c - Namisha (My University, 2015)
The effect of guanidine hydrochloride (GdnHCl) and methylguanidine hydrochloride (MGdnHCl) on the thermal stability and internal dynamics of ferrocytochrome c (ferrocyt c) have been studied at pH 7. Kinetic and thermodynamic parameter measured for CO association reaction of ferrocyt c in the presence of varying concentrations of GdnHCl and MGdnHCl suggests that (i) subdenaturing concentrations of the denaturants decrease the structural fluctuations of the Ω-loop of ferrocyt c, (ii) the extent of decrease in structural fluctuations the Ω-loop is found to be greater for MGdnHCl than GdnHCl, (iii) both entahlpic and entropic effects are responsible for the denaturant mediated reduction the structural fluctuations the Ω-loop, and (iv) at relatively higher concentrations, the denaturing action of these denaturants dominants and result in increase of the structural fluctuations the Ω-loop. Thermodynamic analysis of thermal denaturation curves of ferrocyt c measured in the presence of varying concentrations of GdnHCl and MGdnHCl suggests that these denaturants decrease the thermal stability of protein. These results thus suggest that the denaturant mediated stabilization of the protein is not registered at global level of the protein.
M.Sc. (SCBC)
Keywords: Thermodynamic stability; Enthaplpy; entropy; internal dynamics; SCBC